Biochemical basis of resistance against Blackeye Cowpea Mosaic virus in Cowpea (Vigna unguiculata (L.) Walp.) - Sindhu A.R (Department of Plant Pathology, College of Agriculture, 2001)
The study was undertaken on the blackeye cowpea mosaic virus (BICMV) c ausmg a severe mosaic disease on cowpea (Vigna unguiculat a (L.) Walp). It aimed at locating the sources of heritable resistance and biochemical basis of disease resistance required for formulating effective management practices to check the spread of the disease as well as immunodetection. Among the 66 varieties screened, four were resistant, 29 moderately resistant, 27 moderately susceptible and six susceptible. Six cross combinations were tried and F I hybrid seeds were collected for further evaluation. Biochemical changes indicated a lower carbohydrate content In the resistant variety, compared to susceptible variety. Chlorophyll content decreased in susceptible variety due to virus infection. A lower level of phenol content was observed in resistant variety. Increase in protein content was observed in both susceptible and resistant varieties upon inoculation. The defence related enzymes peroxidase, polyphenol oxidase and phenylalanine ammonialyase were enhanced with virus inoculation in susceptible variety. SDS-PAGE analysis of proteins with samples extracted from plants at 15 DAI showed the presence of two novel virus induced proteins in diseased samples. Native polyacrylamide gel electrophoresis performed for polyphenol oxidase Isozyme revealed significant difference between the genotypes analysed. Five isoforms were found for Sharika and Malika and four for Co-6 and Pallichal local. There was no difference in amino acid pa.ttern in healthy and diseased plant